2021
DOI: 10.1155/2021/6957900
|View full text |Cite
|
Sign up to set email alerts
|

PAK1 Silencing Attenuated Proinflammatory Macrophage Activation and Foam Cell Formation by Increasing PPARγ Expression

Abstract: Macrophage polarization in response to environmental cues has emerged as an important event in the development of atherosclerosis. Compelling evidences suggest that P21-activated kinases 1 (PAK1) is involved in a wide variety of diseases. However, the potential role and mechanism of PAK1 in regulation of macrophage polarization remains to be elucidated. Here, we observed that PAK1 showed a dramatically increased expression in M1 macrophages but decreased expression in M2 macrophages by using a well-established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Macrophages play key roles in inflammation during the development of atherosclerosis. Pak1 expression was reported to upregulate in M1 macrophages but downregulate in M2 macrophages in isolated bone marrow-derived macrophages and peritoneal macrophages of ApoE -/mice [57]. It was also reported that Pak1 knockdown led to increase the anti-inflammatory M2 macrophages activation markers expression (IL-10, arginase-1) and decrease the pro-inflammatory M1 macrophages activation markers expression (IL-6, IL-1β) [57].…”
Section: Pak1 In the Development Of Atherosclerosismentioning
confidence: 75%
“…Macrophages play key roles in inflammation during the development of atherosclerosis. Pak1 expression was reported to upregulate in M1 macrophages but downregulate in M2 macrophages in isolated bone marrow-derived macrophages and peritoneal macrophages of ApoE -/mice [57]. It was also reported that Pak1 knockdown led to increase the anti-inflammatory M2 macrophages activation markers expression (IL-10, arginase-1) and decrease the pro-inflammatory M1 macrophages activation markers expression (IL-6, IL-1β) [57].…”
Section: Pak1 In the Development Of Atherosclerosismentioning
confidence: 75%
“…In addition to the miR-196a-1-3p and miR-3060-3p, miR-485-5p, miR-7219-3p, and miR-103-2-5p were also of interest, and their target gene were predicted using the miRDB database. After screening, we found that a target gene of miR-485-5p, Pak1, the p21 activated kinase, is associated with multiple diseases ( 64 , 65 ) and may play a regulatory role in intestinal inflammation induced by a high-altitude hypoxic environment. Overexpression studies of PAK1, which has been shown to have higher expression in inflammatory bowel disease, showed higher cell proliferation and reduced apoptosis when overexpressed ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence study on PMS women reported a correlation between inflammatory factors elevated levels (IL-2, IL-4, IL-10, and IL-12) and the total symptom score in PMS, and further, higher correlations were noted for IL-12, IL-10, and PMS symptoms [ 14 ]. P21-activated kinase 1 (PAK1) plays a critical role and contributes to various diseases including inflammation, immunosuppression, cancer, viral infection, ageing, and diabetes [ 77 ]. Zeinolabediny et al [ 78 ] discussed the inflammatory disease associated with cardiovascular complications.…”
Section: Literature Review Based On Research Questionsmentioning
confidence: 99%